2012
DOI: 10.4103/2229-5186.99595
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity study of plant Aloe vera (Linn)

Abstract: Background:The objective of this study has been to evaluate the in-vitro antitumor activity of Aloe vera extract of in cultured B16F10 melanoma cell line by measuring cell viability using "Trypan blue exclusion assay" method. Aim: To find out such kind of anticancer drug which is a cheap, safe, less toxic, and more potent drug compared to chemotherapy drug. Materials and Methods: In-vitro antitumor activity cell culture1, drug treatment (standard and test extract) and Trypan blue exclusion assay growth and via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Q4 Q4 cells (Chandu et al 2012). To our knowledge, this is the first study dealing with the mechanism of AVG and AE cytotoxicity.…”
Section: 04%mentioning
confidence: 85%
“…Q4 Q4 cells (Chandu et al 2012). To our knowledge, this is the first study dealing with the mechanism of AVG and AE cytotoxicity.…”
Section: 04%mentioning
confidence: 85%
“…8 Another group of researchers demonstrated a greater cytotoxic effect of aloe vera gel at a 300 µg/mL concentration on melanoma human cancer cell line B16F10. 9 MCF-7, a human breast cancer cell line was found to have stronger cytotoxicity with flavonoids derived from aloe vera gel at an IC50 of 54.97 ± 0.36 µg/mL. 10 These are some of the reported works which suggest that aloe vera is truly a wonder plant in the field of cancer therapy.…”
Section: Introductionmentioning
confidence: 91%
“…Aloe is a plant that is well-known for its medicinal properties and specifically for applications, such as wound healing, as a laxative and for the treatment of skin irritations [26]. Murine melanoma cells were treated with saline extracts of Aloe vera and was it observed that such treatments had reduced cell viability in a concentration dependent manner [234]. Emodin, an active component of Aloe, is a natural hydroxyanthraquinone, which has been studied for its possible anti-melanoma properties.…”
Section: Anti-melanoma Activity Of Crude Plant Extractsmentioning
confidence: 99%